1994
DOI: 10.1055/s-2008-1066119
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Intestinal Dysplasia: Clinical Experience in Italian Patients

Abstract: The authors present a review of 431 children biopsied and studied with the following histochemical and immunohistochemical techniques: 1) acetylcholinesterase activity; 2) alphanaphthylesterase activity; 3) S-100 protein immunohistochemical technique; 4) glyoxylic acid method. Two hundred forty-eight patients of our series presented different forms of dysganglionosis, 12 of them (4.8%) presenting neuronal intestinal dysplasia type B. In 7 cases, NID type B was diffuse, whereas in 5 recto-colonic NID type B was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 3 publications
0
23
0
Order By: Relevance
“…Although there is controversy over the surgical treatment in patients with IND, [11] aggressive surgical management should be adopted because IND has an unpredictable clinical course, and that its management should be dependent on the conditions of each patient.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is controversy over the surgical treatment in patients with IND, [11] aggressive surgical management should be adopted because IND has an unpredictable clinical course, and that its management should be dependent on the conditions of each patient.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for neuronal intestinal dysplasia were: presence of large submucosal ganglia containing >11 neurons/ganglion; presence of “displaced” neurons within the lamina propria and within the musculoaris mucosae; and increased numbers of mucosal nerve fibres as shown by immunohistochemistry 17 18…”
Section: Methodsmentioning
confidence: 99%
“…Csury and Pena [4] reviewed 25 publications and also concluded that there was no correlation between the histological criteria for IND B and the clinical outcome. Several publications disagree on how common IND B is [6,19,26] and this may indicate that this disease has not yet been properly identified or defined.…”
Section: Observed Findings Against Ind Bmentioning
confidence: 90%